PERAN KEJAKSAAN NEGERI SLEMAN DALAM PENYELESAIAN PERKARA PELANGANGGARAN LALU LINTAS - , ANDRI EKA SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the traffic offense matters that had learned by the writer that the offense was belong to misdemeanor because it was case that threatened by criminal confinement at least 3 months and fine as much as 7.500.000 rupiahs. duty of the prosecutor himself in the handling process of criminal offenses and traffic violations which serve receive fines from the offenders for further reported and remitted to the state treasury and the local cash.